Lavender Marriage in the Perspective of Islamic Law: A Case Analysis in Nangka Village, Binjai Utara District - Alawiyah, Nur Suci; Yazid , Imam; Iwan, Iwan (Institut Agama Islam Negeri Kendari, 2025)
Lavender Marriage refers to a marital union undertaken to conceal sexual orientation in order to avoid social stigma. This study analyzes the validity of such a marriage contract under Islamic law and the framework of maqāṣid al-sharī'ah through a case study in Nangka Village, North Binjai District. Employing a juridical-empirical approach with a descriptive-analytical method, data were collected through interviews, observations, and literature review. The findings indicate that although this practice may fulfill the formal requirements of marriage under positive law, it contradicts the essential objectives of marriage in Islam, particularly the establishment of a harmonious family (sakinah, mawaddah, wa rahmah) and the preservation of lineage (ḥifẓ al-nasl). Elements of deception (tadlīs) are present, resulting in greater harm (mafsadah) than benefit (maṣlaḥah), whether morally, socially, or psychologically. The study recommends strengthening premarital counseling, moral development, and public education to prevent similar practices.